2011
DOI: 10.1292/jvms.10-0261
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Spontaneous Chytridiomycosis in Captive Amphibians Using Itraconazole

Abstract: ABSTRACT. We performed this study in order to establish an effective, simple and safe treatment for chytridiomycosis. The subjects were 12 amphibians (11 anurans of 4 different species and 1 urodela) diagnosed with chytridiomycosis by clinical signs and a PCR test. A 0.01% aqueous solution of the antifungal agent itraconazole was used to treat the subjects, and we evaluated the efficacy of treatment by 3 methods: clinical signs, direct microscopy and a nested PCR test. A 10-min immersion in a 0.01% aqueous sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…After the experiment, all tadpoles were successfully treated for 7 d with itraconazole according to Garner et al (2009a) and brought back to their original pond according to permit specifications. Additionally, 89 metamorphs were treated with itraconazole diluted to 0.01% aqueous solution (10 mg l −1 ; Garner et al 2009a, Tamukai et al 2011) for 3 consecutive days before treatment was discontinued because of high mortality. The surviving frogs were returned near their pond of origin.…”
Section: Animal Husbandrymentioning
confidence: 99%
See 1 more Smart Citation
“…After the experiment, all tadpoles were successfully treated for 7 d with itraconazole according to Garner et al (2009a) and brought back to their original pond according to permit specifications. Additionally, 89 metamorphs were treated with itraconazole diluted to 0.01% aqueous solution (10 mg l −1 ; Garner et al 2009a, Tamukai et al 2011) for 3 consecutive days before treatment was discontinued because of high mortality. The surviving frogs were returned near their pond of origin.…”
Section: Animal Husbandrymentioning
confidence: 99%
“…The urgent development of antifungal treatment protocols has resulted in several reports (Nichols et al 2000, Berger et al 2010, Bowerman et al 2010, Pessier & Mendelson 2010, Martel et al 2011, Tamukai et al 2011. Successful trials have been documented in peer-reviewed journals.…”
Section: Introductionmentioning
confidence: 99%
“…(Parker et al 2002), chlor amphenicol (Bishop et al 2009) and the azole-type antifungal drugs itraconazole, fluconazole and vori conazole (Martel et al 2011). An empirically derived treatment protocol using itraconazole ap plied daily as a 100 mg l −1 bath (Nichols et al 2000) has been widely adapted for treatment of chytridiomycosis in captive amphibians (Forzán et al 2008, Gagliardo et al 2008, Pessier 2008, Tamukai et al 2011. Advantages of this protocol are that it is well tolerated by many amphibian species and only a short daily treatment period of 5 to 10 min is needed.…”
Section: Introductionmentioning
confidence: 99%
“…histology). A single report using the more sensitive PCR test to detect evidence of residual Bd infection after treatment examined only a small number of animals (Tamukai et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As the effects of drugs are likely to vary during different developmental stages, the effectiveness and side effects of antifungal agents have generally been evaluated using tadpoles, which are relatively more sensitive to changes in water chemistry (Garner et al 2009, Berger et al 2010, Martel et al 2011. However, with the exception of a study by Tamukai et al (2011) which evaluated the efficacy of itraconazole for the treatment of chytridiomycosis, no known studies have shown that antifungal agents are effective for treating urodeles.The physiology and structural characteristics of urodele skin differ from that of anurans (Warburg et al 1994), and it is unknown whether the methods that are typically used to administer drugs used in anurans are appropriate for use with urodeles. The present study therefore followed the methodology of Tamukai et al (2011), using baths consisting of a 0.01% aqueous solution of itraconazole, which was considered to be both safe and effective.…”
mentioning
confidence: 99%